An Exploration of Citation Policy in History Courses at McMaster University - de Souza, Clare-Marie (Spectrum, 2021)
A brief examination of the reading lists in the syllabi of three history courses taught at McMaster during Spring 2018, Fall 2018, and Fall 2020 through a feminist lens that seeks to determine whether the courses reflect a diverse citation policy in accordance with Sara Ahmed's articulations of what that constitutes in her book Living a Feminist Life. The findings suggest that the classes instead privilege the voices of white men which is in contrast to McMaster's statement on Building an Inclusive Community with a Shared Purpose that articulates their goal of building a diverse McMaster community.